Landscape indicators assessing and monitoring landscape quality - Cassatella, Claudia; Peano, Attilia (Springer Science+Business Media B.V., 2011)
In recent years EU policy towards the landscape has become better defined, whereas at the same time the notion of landscape itself remains elusive. The need for indicators to evaluate and monitor the effects of landscape policies and plans is urgent. What is more, landscape is one of the components considered in environmental reporting, but unlike air, soil, or water, it is difficult to measure using quantitative methods. With studies on landscape indicators being as rare as they are, this volume is an attempt to fill the gap, dealing as it does with the definition and use of specific indicators for landscape assessment and monitoring. To tackle the diverse dimensions of the landscape (whose complexity is well known), the subject is approached by a multidisciplinary team of experts in landscape ecology, landscape history, landscape perception, regional planning, strategic environmental assessment and environmental impact assessment procedures, and multi-criteria assessment methods. Individual chapters include comparative assessments of studies conducted thus far in the EU, as well as detailed analyses of ecological, historical, perceptive, land-use, and economic ways of looking at landscape. As well as providing a rich source of references for researchers studying the landscape from a variety of perspectives, the book will be required reading for European officials involved at any level in planning or assessing the landscape or environment.